Reconstructing Teacher Identity in the Digital Age: A Critical Discourse Study of Influencer Practices in Madrasahs - Yampap, Umar (Molang: Journal Islamic Education, 2025)
This study examines the growing phenomenon of influencer teachers in Islamic educational institutions known as Madrasah, focusing on how they discursively shape and negotiate their professional identities in digital spaces. Using a qualitative approach with Fairclough's critical discourse analysis framework, this study explores the intersection between Islamic scientific values and social media performativity on platforms such as Instagram, TikTok, and YouTube. Research data consists of 30–40 social media posts, non-participatory observations, and semi-structured interviews with 5–8 teacher influencers who meet the following criteria: consistent in creating educational or religious content, having significant digital followers (≥5,000), and receiving academic recognition. Findings reveal that the construction of teacher professionalism in digital spaces is ambiguous: on the one hand, digital engagement expands the dissemination of Islamic knowledge and strengthens teachers' public role; on the other hand, they face algorithmic pressures and performative demands that potentially reduce ethical and epistemic depth. This study identifies ideological tensions and hybrid identities in teachers' digital discourse through Fairclough's three-dimensional framework of text analysis, discourse practices, and social context. It proposes a conceptual model of Reflective Digital Professionalism, encompassing four main dimensions: epistemic identity, digital ethics, media literacy, and reflective criticism. This model expands the traditional understanding of teacher professionalism by incorporating digital socio-cultural dynamics within the context of Islamic education. Practically, this study encourages Islamic educational institutions to develop strategic internal policies that regulate and facilitate teachers' digital role through ethics training, media literacy programs, and reflective community monitoring.